Innovation in the Development of a CO₂ Laser Cutting Machine: Experimentation on Cutting Quality and Machine Precision - Sutopo; Sasongko, Beni Tri; Farih Kurniawan; Virda Hesy Lutviana Saputri; Muhammad Imawan Badranaya; Abdul Aziz Nugroho; Septianto Budi Pranata (Journal of Engineering and Applied Technology, 2025)
In the era of Industry 4.0, CO₂ laser cutting technology has been increasingly adopted across manufacturing, creative industries, and vocational education due to its precision, flexibility, and non-contact process. However, wood-based composites such as Medium Density Fibreboard (MDF) present challenges in laser machining, including thermal deformation, carbonization, and surface damage, necessitating further investigation into process parameters. This study designed and developed a CNC CO₂ Laser Cutting Machine with a 60 W laser source, dimensions of 160 × 100 × 85 cm, and a working area of 110 × 72 × 2 cm, integrating mechanical, optical, and control systems to improve efficiency and precision. The research method involved prototype design, fabrication, assembly, and iterative trials on acrylic, plywood, and MDF, with adjustments made to optimize power, cutting speed, and control stability. Surface roughness tests showed significant variation across materials, with MDF achieving an average Ra value of 6.25 µm (smooth) and acrylic achieving 0.85 µm (very smooth), indicating that acrylic provides superior aesthetic and precision outcomes, while MDF remains suitable for applications with moderate tolerance. The findings highlight that laser parameter optimization is critical for cut quality, and further refinements through jigs/fixtures and the addition of a rotary axis are recommended to enhance structural accuracy and expand application versatility.